2000
DOI: 10.1038/sj.ejcn.1601059
|View full text |Cite
|
Sign up to set email alerts
|

Low intakes of vegetables and fruits, especially citrus fruits, lead to inadequate vitamin C intakes among adults

Abstract: Objective: To determine vitamin C intakes among adults and to identify differences in dietary intake associated with vitamin C consumption. Design: This cross-sectional study compared vitamin C intake, nutrient intake, and food group choices of adults with low (`30 mgad), marginal (30 ± 60 mgad), and desirable ( b 60 mgad) vitamin C intakes. Subjects: Data from 2472 men and 2334 women aged 25 ± 75 y were obtained from the 1994 ± 1996 Continuing Survey of Food Intakes by Individuals (CSFII). Results: Overall, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(26 citation statements)
references
References 20 publications
2
24
0
Order By: Relevance
“…But recently investigators observed inadequate vitamin C intakes in the general population and described the consequences for human health. 8,9 Nishida et al 9 demonstrated, that a decreased vitamin C intake is a contributing risk factor for periodontal disease, especially in smokers. Numerous epidemiological studies have shown that smokers have a higher prevalence and severity of periodontitis when compared to non-smokers.…”
Section: Introductionmentioning
confidence: 99%
“…But recently investigators observed inadequate vitamin C intakes in the general population and described the consequences for human health. 8,9 Nishida et al 9 demonstrated, that a decreased vitamin C intake is a contributing risk factor for periodontal disease, especially in smokers. Numerous epidemiological studies have shown that smokers have a higher prevalence and severity of periodontitis when compared to non-smokers.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, 74.4% of adults had zinc intakes less than half the RDI, 52% had low b-carotene intakes, 44% had low riboflavin intakes and 34% had low vitamin C intakes. Low micronutrient intakes have also been reported by other Indian studies (2) and in Western populations (26,27). The present study group was lactovegetarian, with low consumption of vegetables (66945 g day (1 ) and fruit (66945 g day (1 ), and also of milk and milk products (86967 g day (1 ).…”
Section: Discussionmentioning
confidence: 49%
“…In contrast, marginal ascorbate deficiency, a condition caused by suboptimal vitamin C intake, is much more prevalent. Estimates suggest that > 20% of the UK population and 30%-40% of US adults are affected by subclinical ascorbate deficiency (20,35,42,51). Because this condition is neither associated with overt clinical symptoms nor routinely assessed, its health implications have long been underappreciated.…”
Section: Innovationmentioning
confidence: 99%